Sustainability Strategies of Traditional Vannamei Shrimp Cultivation in East Java: A Case Study in Kudu Hamlet, Lamongan District - Sugiarto, Dwi; Farikhah, Farikhah (Universitas PGRI Semarang, 2024)
The research investigates small-scale farming practices, particularly vannamei shrimp cultivation, in Kudu Hamlet, focusing on how traditional farmers have adopted technology over two decades. Conducted over two years, the study sampled 17 farmers out of 38, analyzing various variables such as age, education, and economic factors. Farmers, predominantly older, have engaged in shrimp farming for nearly two decades, despite fluctuating incomes. Education levels vary, impacting farmers' understanding of new technologies and market trends. Most farmers own their pond land, managing it carefully for shrimp cultivation. Polyculture systems, combining vannamei shrimp with other species, enhance productivity but face challenges like disease outbreaks and market price fluctuations. The choice of feed, predominantly artificial, significantly affects shrimp yields. Farmers also engage in side jobs to supplement income. Overall, enhancing farmers' capacity through education and sustainable practices is crucial for the long-term viability of shrimp farming.